High expression of IL6 and decrease in immune cells in COVID-19 patients combined with myocardial injury - Chen, Tingting; Chen, Haixin; Chen, Ping; Zhu, Linchao; Mao, Wei; Yao, Yimin (Frontiers in Immunology, 2023)
Purpose: Myocardial injury, as a serious complication of coronavirus disease-2019 , increases the occurrence of adverse outcomes. Identification of key regulatory molecules of myocardial injury may help formulate corresponding treatment strategies and improve the prognosis of COVID-19 patients.Methods: Gene Set Enrichment Analysis (GSEA) was conducted to identify co-regulatory pathways. Differentially expressed genes (DEGs) in GSE150392 and GSE169241 were screened and an intersection analysis with key genes of the co-regulatory pathway was conducted. A protein-protein interaction (PPI) network was constructed to screen for key regulatory genes.Preliminarily screened genes were verified using other datasets to identify genes with consistent expression. Based on the hierarchical cluster, we divided the patients from GSE177477 into highand low-risk groups and compared the proportion of immune cells. A total of 267 COVID-19 patients from the Zhejiang Provincial Hospital of Chinese Medicine from December 26, 2022, to January 11, 2023, were enrolled to verify the bioinformatics results. Univariate and multivariate analyses were performed to analyze the risk factors for myocardial injury. According to highsensitivity troponin (hsTnI) levels, patients with COVID-19 were divided into high-and lowsensitivity groups, and interleukin 6 (IL6) expression and lymphocyte subsets were compared.Patients were also divided into high and low groups according to the IL6 expression, and hsTnI levels were compared.Results: Interleukin signaling pathway and GPCR ligand binding were shown to be co-regulatory pathways in myocardial injury associated with COVID-19. According to the hierarchical cluster analysis of seven genes (IL6, NFKBIA, CSF1, CXCL1, IL1R1, SOCS3, and CASP1), patients with myocardial injury could be distinguished from those without myocardial injury. Age, IL6 levels, and hospital stay may be factors influencing myocardial injury caused by COVID-19.Compared with COVID-19 patients without myocardial injury, the levels of IL6 in patients with myocardial injury increased, while the number of CD4 + T cells, CD8 + T cells, B cells, and NK cells decreased (P<0.05). The hsTnI levels in COVID-19 patients with high IL6 levels were higher than those in patients with low IL6 (P<0.05).The COVID-19 patients with myocardial injury had elevated IL6 expression and decreased lymphocyte counts. IL6 may participate in myocardial injury through the interleukin signaling pathway.